2020
DOI: 10.34001/jtn.v2i2.1507
|View full text |Cite
|
Sign up to set email alerts
|

Upaya Guru Dalam Menanamkan Nilai-Nilai Moderasi Beragama Di TPQ Ngerang Tambakromo-Pati

Abstract: Qur’an Learning Institution (TPQ) is an informal institution under of the ministry of religion, such as Ngerang’s TPQ. Ngerang’s TPQ have three educational staff whit 62 students, as for the Ngerang’s TPQ activities direct teaching and learning to various moderation values, namely the implementation of study hour, learning quashes, manners with teachers and study partners. The three activities reflect the moderating values of tolerance, fairness and balance. While the method used in this reaches is qualitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
1
2
0
3
Order By: Relevance
“…The results of the study show that there is a role for Guidance and Counseling teachers in developing the moderation behavior of students at MAN Bintan. These results support previous studies which show that teachers have a role in developing students' religious moderation behavior in the school environment (Atqia & Abdullah, 2021;Haris, 2022;Minarni, 2021;Mubarok et al, 2022;Qowim et al, 2020;Samsul, 2020;Senjaya, 2020).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of the study show that there is a role for Guidance and Counseling teachers in developing the moderation behavior of students at MAN Bintan. These results support previous studies which show that teachers have a role in developing students' religious moderation behavior in the school environment (Atqia & Abdullah, 2021;Haris, 2022;Minarni, 2021;Mubarok et al, 2022;Qowim et al, 2020;Samsul, 2020;Senjaya, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…These strategies seek to foster an inclusive and tolerant environment in educational settings, enabling students to engage with diverse religious perspectives and develop a balanced perspective on their own beliefs. Several previous studies have shown findings related to the role of teachers and religious moderation (Atqia & Abdullah, 2021;Haris, 2022;Minarni, 2021;Mubarok et al, 2022;Qowim et al, 2020;Samsul, 2020;Senjaya, 2020). This paper examines the crucial role played by Guidance and Counseling teachers in fostering students' religious moderation behavior at Madrasah Bintan.…”
Section: Introductionmentioning
confidence: 93%
“…Keenam, moderasi beragama di bidang pendidikan formal (Maghfuri, 2019;Harto & Tastin, 2019;AR, 2020;Salamah, Nugroho & Nugroho, 2020;Amrullah & Islamy, 2021;Anwar & Muhayati, 2021;Chadidjah et al, 2021;Saputra et al, 2021;Umar, Ismail & Syawie, 2021;Liando & Hadirman, 2022) dan non-formal (Nurdin & Naqqiyah, 2019;Asrori, 2020;Aziz, 2020;Khotimah, 2020;Qowim, Suprapto & Nur, 2020;Alim & Munib, 2021;Nugraha, Ahmad & Suhartini, 2021). Memang sudah banyak penelitian yang membahas tema moderasi beragama dalam institusi pendidikan formal dan non-formal, baik di sekolah, kampus, pesantren, TPQ, maupun Madrasah Diniyah.…”
Section: Kelima Moderasi Beragama Menurut Pemikiran Para Tokoh Modera...unclassified
“…Therefore, it becomes necessary if these five values are internalized in religious moderation education. Internalization of the values of fairness, balance, unity and brotherhood can even be found in Islamic religion textbooks, which are taught in various educational institutions, both formal and non-formal (Ainina 2022;Hermawan 2020;Qowim, Suprapto, and Nur 2020;Pujiati 2021).…”
Section: Internalised Religious Moderation Values In Pondok Pesantrenmentioning
confidence: 99%